(untitled) (Ameghiniana, 2013)
BIVALVIA FROM AGUA DEL JAGÜEL FORMATION, LOWER PERMIAN OF MENDOZA, ARGENTINA. - A bivalve fauna from Agua del Jagüel Formation is described and figured; it belongs to the Cancrinella Zone of Lower Permian age. A new species of Cypricardinia? Is recognized and Oriocrassatella sanjuanina? is provisionally referred to a previously known species. Other three species: Sanguinolites sp., Schizodus sp. and Streblochondria? sp., are left with nomina aperta because of ínsufficient materrial.